2008
DOI: 10.3109/10929080802215292
|View full text |Cite
|
Sign up to set email alerts
|

The influence of metal artifacts on navigation and the reduction of artifacts by the use of polyether-ether-ketone

Abstract: Registration is a crucial step in navigation assisted surgery. When performing anatomical pair-point registration, there are several potential sources of error, including inadequate data acquisition, improper segmentation, and distortion resulting from metal artifacts. The aim of this study was to evaluate the influence of metal artifacts on the precision of Iso-C 3D and fluoroscopy-based navigation, and to assess any changes in precision from the use of a newly developed Schanz screw composed of polyether-eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition to distance between camera source and fiducial arrays, Citak et al 70 , 80 performed an investigation to determine the maximum acceptable distance between fixed reference arrays and dynamic “mobile” arrays within the operative field. The results demonstrated a mean registration error of 0.04 mm (0.04-0.05 mm) up to a distance of 200 mm from the patient reference array.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to distance between camera source and fiducial arrays, Citak et al 70 , 80 performed an investigation to determine the maximum acceptable distance between fixed reference arrays and dynamic “mobile” arrays within the operative field. The results demonstrated a mean registration error of 0.04 mm (0.04-0.05 mm) up to a distance of 200 mm from the patient reference array.…”
Section: Resultsmentioning
confidence: 99%
“…The initial registration and intra-operative working accuracy is significantly reduced with localization of arrays greater than 200 mm from the patient reference point. 70 , 80 Moreover, the magnitude of errors secondary to array obstructions differ based on active versus passive markers and distance between arrays. 35 When comparing 2 active Vicon fiducial arrays versus distance, targeting errors increased from 0.47 mm to 1.2 mm, with corresponding stepwise decreases from 5 cm to 0 cm between arrays.…”
Section: Resultsmentioning
confidence: 99%
“…Both techniques, navigation and 3-D imaging itself, do have specific limitations, consequently the combination of both systems might combine these limitations. As reported by some studies in recent publications, limitations of 3-D c-arm navigation have been found in various applications [3,4,6,8].…”
Section: Discussionmentioning
confidence: 99%